An Extremely Rare, Remote Intracerebral Metastasis of Oral Cavity Cancer: A Case Report. (5th October 2013) - Leimert, Mario; Juratli, Tareq A.; Lindner, Claudia; Geiger, Kathrin D.; Gerber, Johannes; Schackert, Gabriele; Kirsch, Matthias
Abstract : Distant brain metastases from oral squamous cell carcinomas (OSCC) are extremely rare. Here we describe a case of a 53-year-old man with a primary OSCC who referred to the neurosurgical department because of epileptic seizures. MR imaging revealed an enhancing lesion in the right parietal lobe. A craniotomy with tumor removing was performed. Histopathological examination verified an invasive, minimally differentiated metastasis of the primary OSCC. The patient refused whole brain radiation therapy and died from pulmonary metastatic disease 10 months after the neurosurgical intervention without any cerebral recurrence. To the authors' knowledge, only two similar cases have been previously reported.